ANALYSIS OF THE MEANING AND EFFECT OF BTS'S SONG "LOVE MYSELF: ANSWER" ON FANDOM ARMY AMONG UNDERGRADUATE STUDENTS - Agustia, Alya Shafira; Pandin, Moses Glorino Rumambo (Academy of Education Journal, 2023)
This research is motivated by the phenomenon of KPOP or Korean Pop, where one of the famous artists is Bangtan Sonnyeondan (BTS), making the Love Yourself album and campaigning for the movement to love yourself at the 73rd UN General Assembly session which was held in New York, United States, on November 24, 2018. One of the songs from the album that was most talked about because of its influence in encouraging self-love is the song Love Myself: Answer. This song will be the object of this research. This study shows how undergraduate students who are members of the ARMY fandom or the designation of BTS fans interpret the song Love Myself: Answer and the effects after interpreting the song. This research was conducted using a qualitative method with a descriptive type of research. Data was collected using the interview method with purposive sampling technique. The population in this study were 5 University students at Airlangga University who met 2 criteria, namely undergraduate students and members of the fandom ARMY. The data analysis technique was carried out using Miles and Huberman analysis. The results showed that the participants interpreted the song as an encouragement to be confident on theirself and caused a motivated and enthusiastic influence to love theirself and they are not feeling lonely after that. We hope that future research can identify reasons people have motivations in life other than music. In this study, only a limited number of subjects were included so that it could not be generalized to a large number of subject groups.